2000
DOI: 10.1073/pnas.230212097
|View full text |Cite
|
Sign up to set email alerts
|

A host–guest system to study structure–function relationships of membrane fusion peptides

Abstract: We designed a host-guest fusion peptide system, which is completely soluble in water and has a high affinity for biological and lipid model membranes. The guest sequences are those of the fusion peptides of influenza hemagglutinin, which are solubilized by a highly charged unstructured C-terminal host sequence. These peptides partition to the surface of negatively charged liposomes or erythrocytes and elicit membrane fusion or hemolysis. They undergo a conformational change from random coil to an obliquely ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
158
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(175 citation statements)
references
References 40 publications
17
158
0
Order By: Relevance
“…Interestingly, influenza A hemagglutinin fusion peptide is inaccessible to membranes at neutral pH; however, a drop of the pH inside the endosome below a critical threshold induces a large conformational change in the parent protein and is subsequently activated by a protease (plasmin) that cleaves the precursor polypeptide (76) into two disulfide-linked polypeptides and a fusion peptide (77). The hemagglutinin fusion peptide has a slightly higher helix content at pH 5 than at pH 7.4, as revealed by comparison of CD spectra (61,74), which are remarkably similar to those for StAP PSI in the present study (Fig. 2) in terms of overall shape (dominant helix content) as well as their x intercepts and superimposed relative spectra (gain of helical structure upon acidification).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, influenza A hemagglutinin fusion peptide is inaccessible to membranes at neutral pH; however, a drop of the pH inside the endosome below a critical threshold induces a large conformational change in the parent protein and is subsequently activated by a protease (plasmin) that cleaves the precursor polypeptide (76) into two disulfide-linked polypeptides and a fusion peptide (77). The hemagglutinin fusion peptide has a slightly higher helix content at pH 5 than at pH 7.4, as revealed by comparison of CD spectra (61,74), which are remarkably similar to those for StAP PSI in the present study (Fig. 2) in terms of overall shape (dominant helix content) as well as their x intercepts and superimposed relative spectra (gain of helical structure upon acidification).…”
Section: Discussionsupporting
confidence: 82%
“…These associations of ␣-helices contain one hydrophobic face, an arrangement similar to StAP PSI with its five helices, hydrophobic inner cavity, and N terminus. An important fusase fusion peptide for virus-cell fusion is the N-terminal portion of influenza A hemagglutinin, which adopts an ␣-helical conformation in lipid bilayers (74), constitutes an autonomous folding unit in the membrane, and catalyzes lipid exchange between juxtaposed membranes (61).…”
Section: Discussionmentioning
confidence: 99%
“…HFP-KKK-UF8L9G10 (sequence AVGIGALFLGFLGAAGSTMGARSKKK) was synthesized with uniformly 13 C, 15 N-labeled amino acids at Phe-8, Leu-9, and Gly-10. Because of the three C-terminal lysines, HFP-KKK dissolved more quickly in aqueous solution than HFP [65].…”
Section: Samplesmentioning
confidence: 99%
“…The IFP-KKK peptide corresponds to the 20 N-terminal residues of the Influenza A hemagglutinin fusion protein plus three C-terminal lysine residues to improve aqueous solubility [65]. There is also a glycine linker in IFP-GKKK.…”
Section: Samplesmentioning
confidence: 99%
“…In each of these soluble ectodomain structures, the protein is trimeric, and its three N-termini (corresponding to about residue 30 in the whole envelope protein) are in close proximity at the end of an in-register helical coiled-coil. These structures end several residues C-terminal of the fusion peptide, and it has therefore been hypothesized that during viral/target cell fusion, at least three fusion peptides insert into the target cell membrane with their C-termini in close proximity.A variety of experimental methods have shown that both the HIV-1 and influenza fusion peptides can assume helical or nonhelical structures in their membrane-associated forms (6,9,10,14,15,17,18,(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50) 1,phosphatidylethanolamine; N-Rh-PE, N-(lissamine rhodamine B sulfonyl)phosphatidylethanolamine; PDB, Protein Data Bank; PI, phosphatidylinositol; POPC, 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine; POPE, 1-palmitoyl-2-oleoyl-snglycero-3-phosphoethanolamine; POPS, 1-palmitoyl-2-oleoyl-sn-glycero-3-phospho-L-serine; rf, radio frequency; RET, resonance energy transfer; REDOR, rotational-echo double resonance; RFDR, radio frequencydriven dipolar recoupling; SEDRA, simple excitation for the dephasing of rotational-echo amplitudes; SIMPSON, simulation program for solidstate NMR spectroscopy; TFA, trifluoroacetic acid; TPPM, two pulse phase modulation; 1D, one dimensional; 2D, two dimensional. …”
mentioning
confidence: 99%